Investigation of Fibrinolytic Activity of Locally Produced Streptokinase - Hamid, Mohsina; Reza Nejadmoqaddam, Mohammad; Rehman, Khalil-ur- (Asian Journal of Chemistry, 2010)
Streptokinase is a common fibrinolytic drug and included in the World Health Organization Model list of essential medicines and widely used in the treatment of acute myocardial infraction following coronary thrombosis. Comparative clinical trials and its cost effectiveness suggest that streptokinase can be the drug of choice for thrembolytic therapy. To obtain the highest amount of the protein and production of active form of streptokinase by hemolytic bacteria need to modify and optimize methods. In the present study native streptokinase was produced indigenously from bacterial source by fermentation biotechnology. After fermentation we, obtained the activity of streptokinase, 1000 U mL-1, specific activity 555.56 U mg-1 with 13.9 fold purification. The purified streptokinase obtained had molecular mass 47 KDa and its Km and Vmax values for lysis of standard fibrinogen (fibrin) clot were 1.93 μg mL-1 and 566.45 IU mg-1 protein, respectively. The activation and inactivation energy were 28.2 and 27.3 KJ mol-1. The most striking findings of this study was the production and purification of native streptokinase by fermentation biotechnology. It could be the proper option to make it economically feasible for the poor heart patients in under developed countries and determine its kinetic parameters because accurate reporting of the characterization of streptokinase preparations is essential for safe and effective therapy.